Product Quality, Price, and Word of Mouth on Customer Purchase Decisions: A Study at Cafe Horas Porong - Yusuf Sobirin; Kumara Adji Kusuma; Lilik Indayani (Journal of Economic, Management, Accounting and Technology (JEMATech), 2026)
This study focused on analyzing the influencing element of purchase decisions in the context of coffee shop at Café Horas Porong with a focus on the effect of product quality, price, and word of mouth on customer purchase decisions at Café Horas Porong. The approach in this research is using quantitative method in which the sample is taken using purposive sampling technique from 96 respondents who have made purchases at Café Horas Porong. The data was analyzed using SmartPLS 3. The results of the study show that the three independent variables, namely product quality, price, and word of mouth, significantly and positively affects customer purchase decision. The implications of this study contribute to the management of Cafe Horas Porong to focus on improving product quality, competitive pricing, and positive word of mouth management in order to increase customer purchase decision. The urgency of this research lies in the need for MSMEs to understand the key factors that can increase competitiveness in the midst of increasingly fierce competition in the coffee shop industry. The limitation of this study lies in the limited location coverage of one coffee shop, so generalization of the results needs to be done with caution. The novelty of this research lies in the simultaneous integration of the three variables in the context of local coffee shop MSMEs in the Porong area.